Analysis and Improvement of Service Quality in Order to Achieve Customer Loyalty (Case Study : Savarna Spa) - Rosita, Rosita; Larso, Dwi (Journal of Innovation, Business and Entrepreneurship, 2016)
Abstract. Service sector has an important role in Indonesian economic growth. 12.82% of the total percentage growth comes from the service healthcare sector. Health care service industry that is currently growing rapidly in Indonesia is a spa business. Spa treatment is needed to refresh the body and feel the relaxation for those who have many activities that drain energy and mind such as college student. In West Java, one of the cities which have a high level of college students population are from Jatinangor with a high level of student activities in Jatinangor. Based on the condition above, Savarna provide a Spa delivery service on Jatinangor. Â As a start-up company who work in service industry, service quality being a critical consideration to attract customer and build customer loyalty. Service quality becomes the valuable factor on the spa business. Factor that can determine customer loyalty in this business is service quality. There is a gap between customer expectations and experiences based on what has their perceived. Research objective of this study is proposed a solution as the improvement of service development on Savarna based on the service quality analysis. In analyzing the issue, researcher use questionnaire which made based on SERVQUAL method and given to the customers who have perceived a treatment service from Savarna. On this study, researcher combined the SERVQUAL method with IPA (Importance Performance Analysis). From the service quality analysis, researcher identifies satisfaction rate and gap score between customer expectation and perceived service on Savarna service quality. The overall satisfaction of service quality assesment is correlated to the analysis of customer loyalty to determine the possibility of customer loyalty based on the satisfaction rate. Based on satisfaction index and gap score analysis, the lowest score of satisfaction are exist on the on-time delivery factor and fast response of customer service contact. Whereas, the cartesius diagram analysis shows three attributes that need a high priority improvement is on the neatness and hygiene service, punctuality on delivery time, and admin can give clear information needed. For the correlation to the customer loyalty, the analysis shows 5 respondents have a 15% possibility to become loyal customer, 27 respondents have a 65% possibility to become loyal customer and 33 respondents have a 95% possibility to become loyal customer.Therefore, researcher purposed several improvements plans to minimize the gap between customer expectation and perceived service and also to maintain customer loyalty which are, Savarna need to add a new item of SOP for the neatness service factor, hire more therapists, add new admin , make a schedule of advertising posts, get more followers on instagram, event promotion, use the attributes of the SERVQUAL method on the questionnaire, and for the future, Savarna should consider to providing additional compensation for the employee and having a legal business license from the government. Â Keywords: Service company, Service quality, start-up, customer loyalty, Savarna spa case study